2014
DOI: 10.1177/1938640014557073
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Fixation Used for Calcaneal Displacement Osteotomies

Abstract: Therapeutic, Level III, Retrospective Comparative Study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 14 publications
1
21
0
Order By: Relevance
“…While this lateral plate and screw construct is more expensive than screws alone, one could argue that the decreased need to return to the operating room for removal of hardware leads to cost savings. Two studies in the literature have described hardware removal rates after calcaneal osteotomy, 4,5 and one of them did show a significantly higher cost associated with procedures that have a higher reoperation rate for hardware removal. Future studies looking at the cost analysis between plates and screws would be beneficial in elucidating this further.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While this lateral plate and screw construct is more expensive than screws alone, one could argue that the decreased need to return to the operating room for removal of hardware leads to cost savings. Two studies in the literature have described hardware removal rates after calcaneal osteotomy, 4,5 and one of them did show a significantly higher cost associated with procedures that have a higher reoperation rate for hardware removal. Future studies looking at the cost analysis between plates and screws would be beneficial in elucidating this further.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that 47% of the headed screws, 11% of the headless screws, and 6% of the lateral plates were removed to address symptoms from the hardware. A few other studies have specifically looked at lateral plates and shown lower rates of hardware removal, ranging from 6% to 22%, 5,8 but these studies had relatively small sample sizes.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have suggested that the need for subsequent surgery for hardware removal may be lower using lateral plate fixation. 1,28 A percutaneously applied blade plate for fixation avoids the need for extensive soft tissue dissection, has a lower profile compared with use of a step plate, allows for compression across the osteotomy, and anecdotally has demonstrated sufficient strength to allow patients to begin weightbearing at 6 weeks in our experience. Lucas and colleagues 28 retrospectively evaluated 228 patients who underwent an open calcaneal osteotomy using a lateral locking plate (EdgeLock Plate; OrthoHelix Surgical Design, Medina, OH) in 63 patients and screws in 165 patients.…”
Section: Fixation Considerationsmentioning
confidence: 86%
“…Lucas et al 8 compared the cost of lateral plates and associated screws ($1157.59) with the cost of calcaneal screws ($247.12), and stated as well that the average cost of hardware removal was $10 937.02. 5 Hardware removal rates were reduced from 19.4% with headed screws to 1.6% in the lateral locking plate group, and the number needed to treat was 6 (CI = 4.1-9.1).…”
Section: Discussionmentioning
confidence: 99%
“…This savings potential is in agreement with that found in other studies in which headed screws were replaced by more modern hardware. 1,2,8 It should be noted that not all procedures involving headed screws will require postoperative screw removal. Foot and ankle surgeons should carefully consider their choice of implant during calcaneal osteotomy procedures because prominent hardware at the back of the heel may require subsequent surgery for removal of hardware.…”
Section: Discussionmentioning
confidence: 99%